PENGENALAN BASIC MICROSOFT SEBAGAI LANDASAN PENTING DALAM MENINGKATKAN KETERAMPILAN DAN PENGETAHUAN KOMPUTER PADA SISWA-SISWI MADRASAH ALIYAH AL RIYADHUL JANNAH - Rifqi Afif; Jordy Martin; Deni Dwi Rifa’i; Muhammad Zaidan Mumtaz; Mohamad Gugun Gunadi; Muhammad Albi Husein; Riski Hidayat; Muhamad Juhaemin; Ibnu Uzair (Abdi Jurnal Publikasi, 2024)
Access to computers in schools in Indonesia is still relatively low. Many students, especially at the secondary level, do not yet have a deep understanding of Microsoft Word. To overcome this challenge, it is important to provide systematic basic training on the use of Microsoft Word in schools, including at Madrasah Aliyah Aliyah Al Riyadhul Jannah. This Community Service Program (PKM) aims to improve the computer skills and knowledge of students at Madrasah Aliyah Aliyah Al Riyadhul Jannah through a basic introduction to Microsoft Word. With the background of low access and understanding of information technology, this activity is designed to provide a better understanding of the use of office applications, especially Microsoft Word. The methods used in implementing this program include consultation with supervising lecturers, field surveys, preparation of materials, implementation of training, and evaluation of activities. The results of the program showed a significant increase in students' understanding of the basic functions of Microsoft Word, as well as high enthusiasm in the practice and question and answer sessions. Positive feedback from participants confirmed that this program was very useful for them in completing academic assignments. It is hoped that this program can be a sustainable initial step in improving the quality of education at Madrasah Aliyah Al Riyadhul Jannah and other schools.